2021
DOI: 10.1027/2698-1866/a000010
|View full text |Cite
|
Sign up to set email alerts
|

Structural Validity and Reliability of the Indonesian Version of PID-5

Abstract: Abstract. Many studies have evaluated the Personality Inventory for DSM-5 (PID-5) validity and reliability. Unfortunately, research on PID-5 in Southeast Asian countries is still limited. This study aimed to identify the structural validity and reliability of the Indonesian version of PID-5. We involved 963 participants, and 68 of these participants filled the PID-5 twice. Facets and domains showed a satisfactory test–retest reliability (median r for facets = .84; median r for domains = .88), and acceptable Mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This finding may be the result of poor reliability of the Suspiciousness scale scores in the present sample. Several studies in Iran (Amini et al, 2021; Hemmati et al, 2021; Lotfi et al, 2018; Somma et al, 2019) and other regions (Adhiatma & Halim, 2021; Labancz et al, 2022; Roskam et al, 2015) address weak internal consistency for Suspiciousness items.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be the result of poor reliability of the Suspiciousness scale scores in the present sample. Several studies in Iran (Amini et al, 2021; Hemmati et al, 2021; Lotfi et al, 2018; Somma et al, 2019) and other regions (Adhiatma & Halim, 2021; Labancz et al, 2022; Roskam et al, 2015) address weak internal consistency for Suspiciousness items.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, systematic reviews have shown that the PID-5 has good internal consistency, with Cronbach's alpha coefficients being greater than.80 in most studies for domain scales and greater than .70 for trait scales (14,15). Studies on its test-retest reliability have shown that domain and trait scores are stable across various time intervals (16)(17)(18)(19)(20)(21)(22). The PID-5 was also shown to have good predictive validity, mostly regarding its capacity to predict categorical PDs (15), but also to predict psychosocial functioning (23) and other mental disorders (24, 25).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the goal to provide measures for diverse contexts has been achieved. In addition to the diverse regional origins (Adhiatma & Halim, 2021; Brauer et al, 2022; Ching et al, 2021; Dierickx et al., 2020; Pfammatter & Schwarz, 2022), other variables have also been addressed. For example, papers adapted measures to children (Golino et al, 2021), migrants (Pfammatter & Schwarz, 2022), specific populations like cyclists (Bishop et al, 2022), or military personnel (Nitzschner et al, 2022).…”
mentioning
confidence: 99%
“…Again, a preliminary, positive conclusion can be drawn. Measures researched capture, for example, cognitive abilities (Brauer et al, 2022; Dahm, 2022; Gnambs et al, 2021; Golino et al, 2021; Krieger et al, 2021), clinically relevant traits (Adhiatma & Halim, 2021; Ching et al, 2021; Lorenz & Algner, 2021), or personality traits (Dierickx et al, 2020; Gallardo-Pujol, Rouco, et al., 2022; Rouco et al, 2022). In addition, specific assessment contexts come from, for example, the educational area (Gnambs et al, 2021) or industrial and organizational psychology (Mitropoulou & Zampetakis, 2022; Nitzschner et al, 2022; Paruzel et al, 2022).…”
mentioning
confidence: 99%